Comparative study of laparoscopic hernia repair versus open hernia repair (Journal of Nobel Medical College, 2018)
Background: Hernia is the abnormal exit of an organ or fatty tissue, such as the bowel, through the weak wall of the cavity in which it normally resides. Repair of inguinal hernia is common surgical  procedures. This study aims to compare between laparoscopic and open hernia repair.Method: Study is non randomized comparative study. Study includes 76 patients who had undergone surgery for hernioplasty. Among them 38 undergone laparoscopic hernioplasty and 38 undergone open hernioplasty from June 2016 to August 2018.Results: Mean hospital stay was 2.95 days in group 1 and 4.03 in group 2 .VAS was found to be 2.45 in group 1 and 5.71 in group 2 which is significantly low in group 1 patients with p